Orphan works: An examination of Indonesian and Malaysian copyright law - Muhamad Khair, Muhamad Helmi; Barizah, Nurul (Jurnal Hukum Novelty, 2025)
Introduction to the Problem: This paper reports findings from research on orphan works in Indonesia and Malaysia. "Orphan works" are copyright-protected works whose copyright holders cannot be contacted or identified by prospective users. Permission to use is essential under the copyright law, but it cannot be obtained in the orphan works context. Presently, there have been no recorded cases of orphan works in either jurisdiction. This situation is further exacerbated by the lack of policies and laws in Indonesia and Malaysia regarding orphan works. Purpose/Study Objectives: On the above basis, this study sought to address the following research questions: (i) What is the current legal treatment to the issue of orphan works in Indonesia and Malaysia? and (ii) How can access to and exploitation of orphan works be legally authorised in Indonesia and Malaysia? Design/Methodology/Approach: The research design was exploratory as this study aimed to examine the current legal treatment of orphan works in light of both jurisdictions' copyright statutes. The doctrinal analysis, as part of normative legal research, was used to answer the first research question by examining Indonesia’s Law Number 28 of 2014 and Malaysia’s Copyright Act 1987. The literature-based research was employed to answer the second research question by extracting information from secondary sources such as reports, textbooks, and journal articles. Findings: This study discovered that Indonesia and Malaysia's existing laws are insufficient to support potential users in exploiting the orphan works. Specifically in Malaysia, the orphan works scenario might be addressed by Section 31 of the Copyright Act 1987, but further improvements could be made to this provision to expand its scope and application. Following that, this study made numerous strategic proposals, including defining a policy for the use of orphan works, establishing a statutory definition of orphan works, and developing an orphan works licensing scheme. Paper Type: Research Article